Use of the Make A Match Learning Model Against Elementary School Students’ Learning Outcomes - Widja Hadi (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2024)
Elementary education is a type of education that focuses on the maturation and development of young learners. The purpose of this study is to ascertain how the make-a-match learning model can be applied to the learning objectives of primary school children. This study is a review of the literature using a qualitative methodology, and it will be explained in a descriptive manner. Understanding and evaluating data sources from scientific publications, theses, proceedings, and books that are relevant to the research topic is how data gathering approaches are carried out. The use of cards in learning activities to create meaningful learning and reinforce students' conceptual understanding is one of the research's findings. in order for students to be joyful and enthusiastic about the subject and to be able to comprehend it well, as shown by an increase in their learning outcomes.